Martin Buber's journey to presence - Huston, Phil (Abrahamic dialogues, 2007)
What does Martin Buber mean, in 'I and Thou', by claiming the one thing that matters is the full acceptance of presence? This work clarifies Buber's predialogical concept of God and is a useful guide to his early writings. It helps readers understand the depth of thought in his masterpiece 'I and Thou'.